Affordable Islamic home financing in Malaysia: a potential synergistic venture between financial cooperatives and cash-waqf institutions - Md Zabri, Mohd Zaidi; Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar (2016)
The current Islamic home financing institutional framework in Malaysia that is almost exclusively dominated by Islamic commercial banks and government-owned home institutions (86% and 10.5% shares of home financing outstanding respectively) are deemed as sustainable in the long run. Economists have long ago identified the contentious relationship between an Islamic commercial bank’s shareholders and its depositors an ‘agency problem’.The Malaysian government on the other hand, is under enormous pressure to gradually reduce its budget deficits. Islamic economics scholars are calling for the third sector economy players such as cooperatives and/or awqaf to address this gap. This conceptual paper aims to present a potential joint-venture by cash waqf institutions and financial cooperative to offer an affordable, musharakah mutanaqisah partnership (MMP) home financing solution to low- and middle-income families in Malaysia. Five critical stakeholders (waqif, cash waqf institutions, financial cooperative, and joint-management committee) form the critical components in this model to offer an alternative, affordable Islamic home financing framework to the current Islamic home financing providers. This model is particularly useful for relevant stakeholders especially within the cooperative society milieu in their effort to help their member-customers to acquire their homes through affordable Islamic home financing.